PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DIKELAS XI MIA SMAN 2 SIAK HULU - Triana, Nela Triana; Rery, R. Usman Rery Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to increase student achievement on the subjectreaction rates in class XI SMAN 2 Siak Hulu. This research is a kind of experimentresearch with pretest-posttest design. The research was conducted in SMAN 2 SiakHulu The samples of this research were the students of class XI MIA 3 as theexperimental class and students of class XI MIA 5 as the control class. Experimentalclass is a class that is applied model of cooperative learning type round table, while thecontrol class was not. Data analysis technique used is the t-test. Based on analysis ofdata obtained tarithmetic> ttable is 2,64> 1,67, means that the application of modelcooperative learning type round table can improve student achievement on the subjectof reaction rates in class XI MIA SMAN 2 Siak Hulu, increase learning of 10,41%.Keywords: Cooperative Learning type Round Table, Student Achievement.